Nation, culture, text : Australian cultural and media studies - Turner, Graeme (Communication and society (Routledge (Firm)), 1993)
Nation, Culture, Text: Australian Cultural and Media Studies is the first collection of cultural studies from Australia, selected and introduced for an international readership. Participating in the d̀e-centring' of cultural studies - considering what perspectives other than the European and the American have to offer - the contributors raise important issues about the role of a national tradition of critical theory, and about the cultural specificity of theory itself. A key theme is the place of the postcolonial nation within contemporary cultural theory - particularly those as.